A detailed CO2(1B2) chemiluminescence chemical kinetics model for carbon monoxide and hydrocarbon oxidation. (1st September 2022) - Liu, Yushuai; Hardalupas, Yannis; Taylor, Alexander M.K.P.
Highlights: A new chemical reaction mechanism was proposed to model CO2 * chemiluminescence in hydrocarbon and carbon monoxide flames. The new mechanism can provide good prediction at both elevated pressures. The performance of new mechanism was validated in premixed CO, CH4, C2 H4, C3 H8 flames. Abstract: The CO2 ( 1 B2 ) - CO2 (X 1 Σ + g ) transition is a source of chemiluminescence from CO and hydrocarbon premixed flames and can be used as a diagnostic; however, its chemistry is not well known due to its broadband nature. Although several attempts have been made to model CO2 ( 1 B2 ) chemiluminescence, none performs well in hydrocarbon flames. We propose a new detailed kinetic model for CO2 ( 1 B2 ) chemiluminescence, based on shock tube experiments in the literature and on opposed flame data presented here. The mechanism consists of 26 reactions which describe the formation of the lower excited state molecule CO2 ( 3 B2 ) (R1), the inter-system crossing reaction between CO2 ( 3 B2 ) and CO2 ( 1 B2 ) (R2), CO2 ( 1 B2 ), the formatting reaction path in hydrocarbon flames (R3), CO2 ( 1 B2 ) radiative quenching (R4) and collisional quenching of CO2 ( 3 B2 ) and CO2 ( 1 B2 ) (R5-R26). The reaction rates constants of R1 and R3 within ± 60% and ± 32% uncertainty, respectively, were determined as follows: CO + O + M = CO2 ( 3 B2 ) + M. k1 = 1 × 10 13 exp(-10/RT) cm 6 mol 2 s −1, KJ mol −1. CH + O2 = CO2 ( 1 B2 ) + H. k3 = 8 × 10 10 cm 3 mol −1 s −1. The mechanism was evaluated against several shock tube experiments at low and elevated pressures and also the CO2 ( 1 B2 )/OH* chemiluminescent intensity ratio for premixed CH4 -air and C3 H8 -air opposed flames measured in the current study. The comparison showed good agreement for CO2 ( 1 B2 ) temporal profiles for CO-based, CH4 -based and C2 H4 -based mixtures. The prediction of temperature dependence of the CO2 ( 1 B2 ) peak intensity for the CH4 -based mixture at both low and elevated pressures was much improved relative to previous models. The CO2 ( 1 B2 )/OH* chemiluminescent intensity ratio for premixed CH4 -air flames predicted by the new model agrees quite well with experiment data, while a small discrepancy remains for C3 H8 -air flames. Overall, the developed CO2 ( 1 B2 ) chemiluminescence model reproduces, a wide range of experimental data and extends knowledge of CO2 ( 1 B2 ) chemistry.